AN OVERVIEW OF HIGHER EDUCATION IN TOURISM AND HOSPITALITY IN PORTUGAL - Moura, Andreia (2024)
Objective: This study evaluates the higher education provision in Portugal's tourism and hospitality sector, examining its evolution and alignment with labor market demands to address the growing skills gap in the industry. Theoretical Framework: The research is grounded in concepts of labor market demands, educational alignment, and workforce development amid digital, societal, and economic transformations. Theories on skills mismatch and human capital development help understand the dynamics between education and employment in this sector. Method: A comprehensive review of higher education offerings in tourism and hospitality in Portugal was conducted, assessing the number of courses and student vacancies while analyzing job market trends. Data were collected from national educational databases and industry reports to examine the evolving relationship between educational programs and labor needs. Results and Discussion: Results indicate a notable increase in tourism and hospitality courses and student vacancies in Portugal’s higher education system, reflecting efforts to cultivate a skilled workforce. However, gaps persist in regional job distribution and the need for specialized training in certain areas. Research Implications: The findings suggest that higher education institutions are progressing in closing the skills gap by offering programs aligned with industry needs, which may influence workforce development strategies and curriculum design. Originality/Value: This study contributes to the literature by analyzing Portugal's educational response to labor market shifts, highlighting the growing alignment between education and industry needs, and providing actionable insights for improving human capital development in tourism and hospitality.